Implementing QR Codes on Student ID for Transactions: TAM Testing Approach - Noviany, Caroline; Daniawan, Benny; Suwitno, Suwitno (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The rapid advancement of technology has had a significant impact on contemporary life. One of the technologies commonly encountered is the Quick Response Code (QR-Code) and Barcode, both of which serve a similar function, that is, to store information represented in the form of squares and lines. Three squares at the corners of the QR-Code are key to ensuring accurate scanning. Universities are educational institutions that provide Student ID Cards as a means of student identification. This research aims to design a transaction system by utilizing QR-Code technology on Student ID Cards for parking and library transactions, as well as creating a transaction system using digitized Student ID Cards. This study employs the Technology Acceptance Model (TAM) testing method to measure the factors influencing users in utilizing the application. The system design successfully incorporates QR-Codes and can be used as a transaction tool. The TAM testing results from 75 respondents regarding system acceptance conclude that the Perceived Ease of Use (PEOU) variable will influence the Perceived Usefulness (PU) variable by 67.4% and affect the Behavioral Toward Using (BITU) variable by 55.1%.